Perancangan Media Pembelajaran Gerakan Semaphore Pramuka Berbasis Augmented Reality Dengan Marker Based Tracking - Hamdani Hamdani; Yeka Hendriyani (UIN Sumatera Utara, 2022)
Scouting is an extracurricular activity that must be carried out in primary and secondary education which has been determined in Permendikbud number 63 the year 2014. The process of delivering scouting material is directly delivered by the coach using the media in the form of a scout pocket book. But in the current condition, students are asked to study independently. Then what makes it difficult for students to learn independently is when they practice the semaphore movement. Therefore, the author provides a solution for media that can be used as a medium for learning the scout semaphore movement. The developed media is an android application with Augmented Reality technology. The use of Augmented Reality-based media can help students learn independently in online learning conditions. The method used in the development of this media is the prototype method, this method consists of three stages, namely listening to customers, designing and making prototypes, and conducting trials. In designing the semaphore movement learning media, it was designed with 3D blender software, unity, vuforia sdk, adobe illustrator. Blender 3D software is used to create 3D semaphore motion objects, Unity is used to create augmented reality-based android applications, Vuforia is used as a marker database and Adobe Illustrator is used to design markers and display applications. The final result of this final project is an Augmented Reality-based learning media for scout semaphore movements. Keywords: Scouts, Android, Augmented Reality, Unity, Prototype